Hydrodynamic and Morphological Adaptation of Two Consecutive Sharp Bends of the Middle Yangtze River to Upstream Damming - Xin Liu; Junqiang Xia; Shanshan Deng; Meirong Zhou; Beiping Mao; Koen Blanckaert (Water Resources Research)
Abstract It remains an open question how the hydrodynamics and morphology in sharp meander bends adapt to the changes in flow and sediment conditions induced by upstream damming. This study reports a comprehensive investigation into the morphological changes, patterns of mean and secondary flows and sediment transport around two consecutive sharp bends in the Middle Yangtze River (MYR), and explains these changes from the viewpoint of flow‐sediment transport‐morphology interaction based on field measurements. With the Three Gorges Project operation, the MYR suffered a remarkable channel degradation due to a sudden decrease of incoming sediment discharge. The point bars were removed, and outer‐bank benches (OBB) formed upstream of the bend apices, which resulted in quite different flow and sediment transport patterns in the bends. The highest velocity zones and center‐region cells of secondary flow were more toward the inner bank due to the lack of point bars, and the outward migration of momentum was delayed. Flow recirculation zones were observed over the OBBs, covering 12%–58% of the channel width. The transport rates of suspended load accounted for 98% of the total sediment load, and the outward shift of the highest transport rate zone was confined by the OBBs, which reduced the effective width of sediment transport. These changes in flow and sediment transport re‐inforced the morphological changes around the sharp bends: the velocity redistribution and evolution of scour factor lagged more behind planform curvature, which further promoted the erosion of point bars and the development of OBB.